Electron barrier formation at the organic-back contact interface is the first step in thermal degradation of polymer solar cells - Sachs-Quintana, I. T.; Heumüller, Thomas; Mateker, William R.; Orozco, Darian E.; Cheacharoen, Rongrong; Sweetnam, Sean; Brabec, Christoph; Mcgehee, Michael D. (Advanced Functional Materials, 2014)
Long-term stability of polymer solar cells is determined by many factors, one of which is thermal stability. Although many thermal stability studies occur far beyond the operating temperature of a solar cell which is almost always less than 65 °C, thermal degradation is studied at temperatures that the solar cell would encounter in real-world operating conditions. At these temperatures, movement of the polymer and fullerenes, along with adhesion of the polymer to the back contact, creates a barrier for electron extraction. The polymer barrier can be removed and the performance can be restored by peeling off the electrode and depositing a new one. X-ray photoelectron spectroscopy measurements reveal a larger amount of polymer adhered to electrodes peeled from aged devices than electrodes peeled from fresh devices. The degradation caused by hole-transporting polymer adhering to the electrode can be suppressed by using an inverted device where instead of electrons, holes are extracted at the back metal electrode. The problem can be ultimately eliminated by choosing a polymer with a high glass transition temperature. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: degradation; interfaces; lifetime; organic photovoltaics; stability